Relationship Between Husband Support and the Use of Postpartum Contraceptives: A Literature Review - Nova Anggaraini; Is Susiloningtyas (OVUM : Journal of Midwifery and Health Sciences, 2026)
The postpartum period is a critical phase in reproductive health because the risk of closely spaced pregnancy increases when appropriate contraception is not used. The coverage of postpartum contraceptive use remains suboptimal and is influenced by multiple factors, including husband support in the decision-making process. This study aimed to analyze the relationship between husband support and the use of postpartum contraception based on recent empirical evidence. Methods: This study applied a literature review method by analyzing 10 research articles obtained from PubMed, Google Scholar, and ScienceDirect using the keywords "husband support," "postpartum contraception," and "postpartum family planning" published between 2021 and 2026. Inclusion criteria were primary research articles-quantitative or mixed methods design, full text availability, and articles written in English or Indonesian. Results and Discussion: Most studies used a cross-sectional design with Chi Square and logistic regression analysis. The majority of articles reported p values less than 0.05, indicating a significant relationship between husband support and postpartum contraceptive use. Influential forms of support included emotional, informational, instrumental, and joint decision-making support. Several studies also reported that women who received strong husband support were more than twice as likely to use postpartum contraception. Conclusion: Husband support is a key determinant in increasing the use of postpartum contraception. Integrating couple-based counseling into antenatal and postnatal care is necessary to strengthen the effectiveness of postpartum family planning programs.